Analysis of Patient Satisfaction with BPJS (Social Security Administration) and Non-BPJS Health Services - Yahya, Khairuman; Juliani, Annisa; Fajira, Elsa (Yayasan Adra Karima Hubbi, 2024)
Background. Patient satisfaction is an important issue in hospitals, both in Indonesia and abroad. Low satisfaction levels can negatively impact the development of hospitals. Patient satisfaction is a key indicator in health services, as it reflects patients' assessment of the services received, compared to their expectations of services in health facilities. Purpose. This study aims to determine the difference in service satisfaction between BPJS and non-BPJS patients in hospitals, as an effort to identify factors that affect patient satisfaction in both groups. Method. The method used in this study is a literature review, in which various journals from various sources relevant to this topic are analyzed. This approach allows for a deeper understanding of the differences in satisfaction levels between BPJS and non-BPJS patients based on previous studies. Results. The results of this study show that there is a difference in satisfaction levels between BPJS and non-BPJS patients. Factors such as waiting times, quality of interaction with health workers, and availability of facilities affect the difference in satisfaction in these two patient groups. Conclusion. This study concludes that the difference in service satisfaction between BPJS and non-BPJS patients shows the importance of service adjustment based on the needs and expectations of each patient group. Improving the quality of service for BPJS and non-BPJS patients is expected to increase overall patient satisfaction, which in turn supports the development of the hospital in the long term.